Optimalisasi Keterampilan Literasi Siswa SMP NW Mataram Melalui Program Klinik Literasi - Hidayati, Parni; Magdalena, Magdalena; Nur Aisyah, St.; Fatiha Putri Aura Diva; Rosyihan Anwar, Iklima; Sri Kusuma Wardani, Ketut (Rengganis Jurnal Pengabdian Masyarakat, 2024)
The Literacy Clinic is a program to improve students' literacy skills, with a focus on guiding and teaching students who are deficient in reading, writing, and others. This service aims to optimize the literacy skills of class VIII students at SMP NW Mataram through the implementation of a literacy clinic program. The method for implementing the literacy clinic program uses three stages: observation, implementation and evaluation. Data was collected through observation, interviews, Pre-Test and Post-Test. The results of the service are that there are still students who are not fluent in reading which was discovered through interviews and observations. This is also proven by the Pre-Test results which show the percentage of students answering correctly 18%. Therefore, the author designed and implemented a Literacy Clinic program that could improve students' literacy skills. After carrying out the Literacy Clinic, the students then answered the Post-Test questions with the percentage of students answering correctly 49%. Based on this description, it can be concluded that the existence of a literacy clinic program can optimize the Literacy Skills of SMP NW Mataram Students